2021
DOI: 10.1155/2021/6659908
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Clues of Regulatory Roles of Circular RNAs through Modulating Oxidative Stress: Focus on Neurological and Vascular Diseases

Abstract: Circular RNAs (circRNAs) are novel noncoding RNAs that play regulatory roles in gene expression. Dysregulation of circRNAs is associated with the development and progression of several diseases, such as diabetes mellitus, nervous system diseases, cardiovascular diseases, and cancer. CircRNAs functionally participate in cell physiological activities through various molecular mechanisms. However, these molecular mechanisms are unclear. Oxidative stress is an essential factor in the pathogenesis of various diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 112 publications
(150 reference statements)
0
14
0
Order By: Relevance
“…Several miRNAs can be oxidized themselves and regulate the expression levels of many genes involved in antioxidant defense pathways [63]; for example, oxidative modification of miR-184 reduced expression levels of Bcl-xL and Bcl-w due to misrecognitions, leading to apoptosis [64], and miR-27a influences redox homeostasis due to reduced expression levels of nuclear factor E2-related factor 2 (NRF2), which is a major regulator of antioxidant elements [65]. In addition, several circRNAs can be related to neurodegeneration via modulation of oxidative stress; for example, circHIPK3 can regulate oxidative stress due to work through a signaling network that consists of circHIPK3 and miR-29a [66].…”
Section: Oxidative Rna Damagementioning
confidence: 99%
“…Several miRNAs can be oxidized themselves and regulate the expression levels of many genes involved in antioxidant defense pathways [63]; for example, oxidative modification of miR-184 reduced expression levels of Bcl-xL and Bcl-w due to misrecognitions, leading to apoptosis [64], and miR-27a influences redox homeostasis due to reduced expression levels of nuclear factor E2-related factor 2 (NRF2), which is a major regulator of antioxidant elements [65]. In addition, several circRNAs can be related to neurodegeneration via modulation of oxidative stress; for example, circHIPK3 can regulate oxidative stress due to work through a signaling network that consists of circHIPK3 and miR-29a [66].…”
Section: Oxidative Rna Damagementioning
confidence: 99%
“…They display cell-specific, and tissue-specific/developmental-stage-specific expression. Their biogenesis appears dissimilar from the canonical splicing of linear RNAs and is controlled by specific cis-acting elements and trans-acting factors [99][100][101][102]. CircRNAs act as regulators of diverse biolog-…”
Section: Use News Regulators Of Os For Developing Targeted Treatmentsmentioning
confidence: 99%
“…ical and pathological processes by sponging miRNAs, binding to RBP, that are as abovementioned regulators of splicing and transcription, modifiers of parental gene expression, and regulators of protein translation or being translated into peptides in various diseases[99][100][101][102]. CircRNAs have been detected in exosomes and body fluids, including human blood, saliva, and cerebrospinal fluids, evidencing that these exo-circRNAs can represent both disease biomarkers and novel therapeutic targets.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…15 All these functions suggested that circRNAs may be potential novel diagnostic and prognostic biomarkers of disease. 16 So far, it has been reported that circRNAs are extensively involved in the processes of many human diseases, including a variety of cancers, [17][18][19] neurological disorders, 20,21 cardiovascular disease, [22][23][24] immune disease 25 and so on. Similarly, many circRNAs have been proved to be regulate the process of PCOS, such as circASPH, 26 circLDLR 1 and circPUM1.…”
Section: Introductionmentioning
confidence: 99%